Colonization factors of Campylobacter jejuni in the chicken gut - Hermans David (Veterinary Research, 2011)
Abstract Campylobacter contaminated broiler chicken meat is an important source of foodborne gastroenteritis and poses a serious health burden in industrialized countries. Broiler chickens are commonly regarded as a natural host for this zoonotic pathogen and infected birds carry a very high C. jejuni load in their gastrointestinal tract, especially the ceca. This eventually results in contaminated carcasses during processing. Current intervention methods fail to reduce the colonization of broiler chicks by C. jejuni due to an incomplete understanding on the interaction between C. jejuni and its avian host. Clearly, C. jejuni developed several survival and colonization mechanisms which are responsible for its highly adapted nature to the chicken host. But how these mechanisms interact with one another, leading to persistent, high-level cecal colonization remains largely obscure. A plethora of mutagenesis studies in the past few years resulted in the identification of several of the genes and proteins of C. jejuni involved in different aspects of the cellular response of this bacterium in the chicken gut. In this review, a thorough, up-to-date overview will be given of the survival mechanisms and colonization factors of C. jejuni identified to date. These factors may contribute to our understanding on how C. jejuni survival and colonization in chicks is mediated, as well as provide potential targets for effective subunit vaccine development.